Nietzsche e pessoa: um diálogo trágico entre filosofia e literatura - BATISTA, Francisco Lobo (Universidade Federal do Pará, 2018)
This study seeks to approximate two of the biggest critics of modernity, Nietzsche and Fernando Pessoa, from themes that are common to them and, in general terms, proposed a dialogue between philosophy and art, more precisely, between philosophy and literature. From the literature reviewed, we can say that Pessoa was an involuntary nietzschean who search for in the subjectivity criticism, in metaphorical language understanding and in the image of the child, the overcoming of metaphysics. In this way, Nietzsche, a deleuzian perspective, worked with several conceptual characters and, though not as radical as Pessoa form, thought from various heteronyms.